A catalytically active electrode and its preparation method and application

By using solvent heat and calcination to grow the lanthanum-doped tin dioxide-antimal coating on the surface of the titanium-based current collector, the problems of insufficient electrocatalytic activity and poor conductivity of the existing titanium-based metal oxide electrodes are solved, and efficient organic degradation and electrode life extension are achieved.

CN115974236BActive Publication Date: 2025-03-25GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211729983.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2025-03-25
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

The existing titanium-based metal oxide coating electrodes have problems such as insufficient electrocatalytic activity, poor conductivity and potential metal ion dissolution pollution, making it difficult to effectively deal with difficult-to-degrade organic wastewater.

Method used

The lanthanum-doped tin dioxide-antimal coating was uniformly grown on the surface of the titanium-based current collector by solvent heat and calcination to form a titanium-based lanthanum-doped tin dioxide-antimal electrode with uniform surface layer.

Benefits of technology

It significantly improves electrocatalytic activity and conductivity, enhances the degradation efficiency of organic matter, extends the service life of the electrode, and reduces material costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115974236B_ABST
    Figure CN115974236B_ABST
Patent Text Reader

Abstract

The present invention provides a catalytically active electrode and a preparation method and application thereof. The catalytically active electrode comprises a titanium-based current collector and a tin dioxide layer doped with lanthanum and antimony located on the titanium-based current collector. The preparation method comprises: placing the titanium-based current collector in a mixed solution containing tin, antimony and lanthanum elements for a solvothermal reaction and then calcining to obtain the catalytically active electrode. The present invention adopts a solvothermal method to react at a specific temperature and combines calcination to obtain a titanium-based lanthanum-doped tin dioxide-antimony electrode, which greatly improves the catalytic degradation effect of antibiotic wastewater simulated by a norfloxacin original drug solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical water treatment, and relates to a catalytically active electrode, and in particular to a catalytically active electrode and a preparation method and application thereof. Background Art

[0002] Electrocatalytic oxidation technology is a popular technology for treating refractory organic wastewater. This technology degrades toxic and harmful refractory organic molecules into small organic molecules or directly mineralizes them into carbon dioxide and water by releasing strong oxidizing groups from reaction electrodes. The electrochemical oxidation process does not require the addition of other agents, and no other secondary pollutants are produced. It has the advantages of mild reaction conditions, high pollutant removal efficiency, and easy operation.

[0003] A key to the application of electrochemical oxidation technology is the development of electrode materials. Different anode materials will have different degradation effects on different types of pollutants. Only suitable anode materials can achieve the ideal pollutant degradation effect. At present, the most widely used anode materials are titanium-based oxide coated electrodes, which mainly include ruthenium oxide series, iridium oxide series, tin antimony oxide series, lead dioxide series, etc. Titanium ruthenium and iridium electrodes have better effects, but the cost of using precious metals is relatively high; titanium lead dioxide electrodes have high catalytic activity and strong chemical stability, but there is a risk of lead dissolution pollution; titanium tin dioxide electrodes are currently the most widely used electrocatalytic sewage treatment anodes. Generally, a certain proportion of antimony needs to be added to tin dioxide to increase conductivity and electrocatalytic activity. However, titanium tin oxide antimony electrodes still have shortcomings such as insufficient electrocatalytic activity and poor conductivity.

[0004] CN108914122A discloses a method for preparing a titanium-based lead dioxide anode, which includes the following steps: pre-treating the titanium-based substrate; dissolving tin tetrachloride and antimony trichloride in isopropanol containing hydrochloric acid, and coating the titanium plate substrate surface, drying and roasting to obtain an electrode with a tin antimony oxide bottom layer; using the electrode with the tin antimony oxide bottom layer as the anode and the titanium plate as the cathode, electro-depositing an αPbO2 intermediate layer in a sodium hydroxide plating solution in which PbO is dissolved; using the titanium plate as the anode and the titanium plate as the cathode, electro-depositing a modified βPbO2 active layer containing cerium dioxide, erbium, and fluorine to obtain the titanium-based lead dioxide anode. The lead dioxide electrode plate prepared by the method has a uniform and dense surface, a long service life, and a very good use effect, but the lead dioxide electrode has a pollution problem caused by the dissolution of lead ions.

[0005] CN106241970A discloses an aluminum-doped tin dioxide electrocatalytic anode, which is composed of a titanium substrate and an anode coating coated on the titanium substrate, wherein the anode coating is made of the following components in molar fractions: 600-700 parts of citric acid, 100-300 parts of ethylene glycol, 100-200 parts of tin tetrachloride, 5-10 parts of antimony trichloride, and 1-3 parts of aluminum trichloride. The aluminum-doped tin dioxide electrocatalytic anode prepared by the invention has high catalytic activity, has a good degradation effect on phenol wastewater, and has low cost due to the use of metal aluminum-doped tin dioxide electrocatalytic anode. However, aluminum has limited improvement on the electrocatalytic activity of tin dioxide and the service life of the electrode.

[0006] At present, titanium-based metal oxide coated electrodes have been widely studied at home and abroad. In view of the problems of low electrocatalytic activity, short life, poor electrode conductivity, potential metal ion dissolution pollution, etc. of titanium-based metal oxide coated electrodes, further exploration of the development of new electrodes is needed. Summary of the invention

[0007] The object of the present invention is to provide a catalytically active electrode with high electrocatalytic activity, long life and good electrode conductivity, and a preparation method and application thereof.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] One of the objects of the present invention is to provide a catalytically active electrode, which comprises a current collector and a lanthanum- and antimony-doped tin dioxide layer located on the titanium-based current collector.

[0010] In the present invention, a lanthanum-doped tin dioxide-antimony electrode is prepared on a titanium-based current collector. The obtained electrode has the characteristics of small surface crystal particle size, large specific surface area, and high oxygen evolution potential, and the electrocatalytic activity and electrical conductivity are significantly improved. The prepared high catalytic activity electrode can be used for the efficient treatment of organic matter in high-salt wastewater, and has very broad application prospects.

[0011] As a preferred technical solution of the present invention, the lanthanum and antimony are uniformly doped in the tin dioxide layer.

[0012] Preferably, the molar ratio of lanthanum to antimony is (5-10):10, wherein the molar ratio can be 5:10, 6:10, 7:10, 8:10, 9:10 or 10:10, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0013] Preferably, the molar percentage of lanthanum in the tin dioxide layer is 1-10%, wherein the molar percentage can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0014] A second object of the present invention is to provide a method for preparing a catalytically active electrode as described in the first object, the preparation method comprising:

[0015] The titanium-based current collector is placed in a mixed solution containing tin, antimony and lanthanum to undergo a solvothermal reaction, and then calcined to obtain the catalytically active electrode.

[0016] The present invention adopts a solvent thermal and calcination method to uniformly grow a lanthanum-doped tin dioxide-antimony coating on the surface of a titanium-based current collector. Precursor solutions are prepared with different tin (Sn) sources, antimony (Sb) sources, and lanthanum (La) sources, and a solvent thermal reaction and calcination are combined to control the appropriate reaction temperature and pressure for homogeneous crystallization and sintering conversion, so that the Sn-Sb-La coating is uniformly covered on the surface of the titanium-based electrode. The present invention adopts a solvent thermal method to react at a specific temperature and combines calcination to obtain a titanium-based lanthanum-doped tin dioxide-antimony catalytically active electrode, which has simple steps and is easy to operate. Lanthanum is a doping raw material and the material cost is low.

[0017] As a preferred technical solution of the present invention, the preparation method of the mixed solution is: adding a tin source, an antimony source and a lanthanum source into an acidic solution and mixing them to obtain the mixed solution.

[0018] As a preferred technical solution of the present invention, the tin source includes crystalline tin tetrachloride.

[0019] Preferably, the antimony source comprises antimony trichloride.

[0020] Preferably, the lanthanum source comprises a lanthanum salt compound, and the lanthanum salt compound comprises lanthanum nitrate and / or lanthanum chloride, preferably lanthanum nitrate.

[0021] Preferably, the atomic molar concentration ratio of the tin source, antimony source and lanthanum source is 100:10:(5-10), wherein the atomic molar concentration ratio can be 100:10:5, 100:10:6, 100:10:7, 100:10:8, 100:10:9 or 100:10:10, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] Preferably, the solvent of the acidic solution is an organic solvent, and the organic solvent includes ethanol.

[0023] Preferably, the solute of the acidic solution is hydrochloric acid.

[0024] Preferably, the concentration of the hydrochloric acid in the mixed solution is 0.5-1 moL / L, wherein the concentration may be 0.5 moL / L, 0.6 moL / L, 0.7 moL / L, 0.8 moL / L, 0.9 moL / L or 1 moL / L, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] As a preferred technical solution of the present invention, the mixing includes ultrasonic mixing.

[0026] Preferably, the ultrasonic mixing time is 10 to 30 min, wherein the time can be 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min, 26 min, 28 min or 30 min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] Preferably, the ultrasonic power of the ultrasonic mixing is 350-450 W, wherein the ultrasonic power can be 350 W, 360 W, 370 W, 380 W, 390 W, 400 W, 410 W, 420 W, 430 W, 440 W or 450 W, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] As a preferred technical solution of the present invention, the titanium-based current collector includes a titanium mesh, a titanium plate or a titanium foil.

[0029] Preferably, the titanium-based current collector is pretreated, and the pretreatment includes: first washing the titanium-based current collector and then acid washing the titanium-based current collector.

[0030] Preferably, the first cleaning comprises: sequentially performing acetone ultrasonic cleaning for 10 to 30 minutes, rinsing with anhydrous ethanol and rinsing with deionized water on the titanium-based current collector. The cleaning time can be 10 minutes, 12 minutes, 14 minutes, 16 minutes, 18 minutes, 20 minutes, 22 minutes, 24 minutes, 26 minutes, 28 minutes or 30 minutes, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0031] Preferably, the acid in the pickling comprises 10% oxalic acid.

[0032] Preferably, the pickling is a slightly boiling heat treatment in acid, and the time of the slightly boiling heat treatment is 1.5 to 2.5 hours, wherein the time can be 1.5 hours, 1.6 hours, 1.7 hours, 1.8 hours, 1.9 hours, 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours or 2.5 hours, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] Preferably, a first cooling is performed after the pickling, and after the first cooling, the titanium-based current collector is stored in anhydrous ethanol.

[0034] As a preferred technical solution of the present invention, the solvent thermal reaction is carried out in a reactor.

[0035] Preferably, the temperature of the solvothermal reaction is 150-190°C, wherein the temperature may be 150°C, 160°C, 170°C, 180°C or 190°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] If the temperature of the solvent thermal reaction in the present invention is too high, the particles on the electrode surface will become larger, resulting in a decrease in the specific surface area of ​​the electrode; if the temperature is too low, it will be difficult to form a uniform surface structure.

[0037] Preferably, the solvent thermal reaction time is 8 to 16 hours, wherein the time can be 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours or 16 hours, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] As a preferred technical solution of the present invention, the solvent thermal reaction is followed by a second cooling, a second cleaning and drying.

[0039] Preferably, the second cleaning comprises cleaning the electrode surface with deionized water and / or anhydrous ethanol.

[0040] Preferably, the dried electrode is calcined.

[0041] Preferably, the calcination atmosphere is air.

[0042] Preferably, the calcination temperature is 400-600°C, wherein the temperature may be 400°C, 420°C, 440°C, 460°C, 480°C, 500°C, 520°C, 540°C, 560°C, 580°C or 600°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] Preferably, the calcination time is 1 to 3 hours, wherein the time can be 1 hour, 2 hours or 3 hours, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] A third object of the present invention is to provide an application of a catalytically active electrode as described in the first object, wherein the catalytically active electrode is applied in the field of electrochemical water treatment technology.

[0045] Compared with the prior art, the present invention has the following beneficial effects:

[0046] (1) The present invention prepares a tin (Sn) source, an antimony (Sb) source, and a lanthanum (La) source into a precursor solution, and uniformly grows a Sn-Sb-La coating on the surface of a titanium-based current collector through a high-temperature and high-pressure reaction. A titanium-based lanthanum-doped tin dioxide-antimony electrode with a uniform surface layer is obtained by heat treatment at a specific temperature using a solvothermal method. The obtained electrode has the characteristics of smaller and more uniform crystal particle size, larger specific surface area, and higher oxygen evolution potential, thereby increasing the contact between the target pollutant and the electrode, improving the mass transfer rate during the reaction process, and improving the electrocatalytic reaction activity.

[0047] (2) The present invention adopts a solvothermal method to react at a specific temperature and combine calcination to obtain a titanium-based lanthanum-doped tin dioxide-antimony electrode, which has simple steps and is easy to operate. The cost of lanthanum as a doping raw material is low. At the same time, the method only needs to be powered on at room temperature and pressure to degrade organic matter. The reaction conditions are mild, the reaction device is simple, and it is relatively easy to expand production.

[0048] (3) Compared with the conventional titanium-based tin dioxide-antimony electrode, the high catalytic activity titanium-based lanthanum-doped tin dioxide-antimony electrode obtained by the present invention has a greatly improved catalytic degradation effect on antibiotic wastewater simulated by norfloxacin original drug solution under certain conditions, and the degradation rate can be as high as 92%. In addition, the electrode prepared by the present invention can also be used to treat other toxic, harmful and difficult to biodegrade organic matter in the water environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 It is the X-ray diffraction pattern of the catalytically active electrode of Example 1 of the present invention and Comparative Example 1.

[0050] Figure 2 It is the removal rate curve of the degradation process of antibiotic wastewater simulated by norfloxacin solution in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0051] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0052] Example 1

[0053] This embodiment provides a catalytically active electrode, which includes a titanium-based current collector and a tin dioxide layer uniformly doped with lanthanum and antimony and located on the titanium-based current collector.

[0054] The molar ratio of the lanthanum element to the antimony element is 7.5:10. The molar percentage of the lanthanum element in the tin dioxide layer is 7.5%.

[0055] This embodiment also provides a method for preparing the above-mentioned catalytically active electrode, the preparation method comprising:

[0056] Pretreatment of titanium-based current collector: The electrode substrate uses titanium mesh with a specification of 30mm X 20mm X 1mm, which is sequentially subjected to the first cleaning and acid washing. First cleaning: Place the titanium mesh in a beaker filled with analytical pure acetone so that each titanium mesh is dispersed without overlapping, put the beaker into an ultrasonic cleaning machine for cleaning for 30 minutes, then take it out, rinse it three times with ethanol, and finally rinse it with deionized water; Acid washing: Immerse the titanium mesh cleaned with acetone in an oxalic acid solution with a mass concentration of 10%, so that each titanium mesh is dispersed without overlapping, heat it in a water bath to 97°C and slightly boil it, keep it for 2 hours, then stop heating, take it out after cooling, place it in a beaker containing deionized water for ultrasonic cleaning for 10 minutes, and then place it in anhydrous ethanol for storage to obtain a titanium mesh that has been pretreated.

[0057] The preparation of the mixed solution containing tin, antimony and lanthanum comprises: adding hydrochloric acid to anhydrous ethanol to prepare a 1 mol / L hydrochloric acid ethanol solution, dissolving crystalline tin tetrachloride, antimony trichloride and lanthanum nitrate in the hydrochloric acid ethanol solution according to a molar ratio of Sn:Sb:La=100:10:7.5, sealing and ultrasonically treating for 15 minutes to obtain the mixed solution.

[0058] The pretreated titanium-based current collector was placed in the polytetrafluoroethylene liner of the reactor, 35 mL of a mixed solution containing tin, antimony and lanthanum elements was added, the stainless steel shell of the high-pressure reactor was tightened, and the reactor was placed in an electric blast drying oven for reaction at 180°C for 12 hours. After the solvent thermal reaction was completed, it was cooled to room temperature and taken out. After being rinsed with deionized water and dried, the electrode was placed in a 550°C tubular furnace for air calcination for 2 hours, cooled to room temperature and taken out to obtain a titanium-based lanthanum-doped tin dioxide-antimony electrode with high catalytic activity.

[0059] Example 2

[0060] In this example, except that the molar ratio of crystalline tin tetrachloride, antimony trichloride and lanthanum nitrate is replaced with 100:10:10, other conditions are the same as those in Example 1.

[0061] Example 3

[0062] In this embodiment, the conditions are the same as those in Embodiment 1 except that the reaction kettle is placed in an electric blast drying oven at 180° C. for 8 hours instead of 12 hours.

[0063] Example 4

[0064] In this embodiment, except that the electrode is placed in a tube furnace and calcined in air at 500° C. for 1 hour instead of being placed in a tube furnace and calcined in air at 550° C. for 2 hours, other conditions are the same as those in Embodiment 1.

[0065] Example 5

[0066] Except that the titanium-based current collector is not pretreated, other conditions in this embodiment are the same as those in Embodiment 1.

[0067] Example 6

[0068] In this embodiment, except that the acid washing is not performed in the pretreatment of the titanium-based current collector, other conditions are the same as those in Embodiment 1.

[0069] Comparative Example 1

[0070] In this comparative example, a titanium-based tin dioxide-antimony catalytic active electrode was prepared without adding lanthanum element to the active material layer, that is, without adding lanthanum nitrate during the preparation process. Other conditions were the same as those in Example 1.

[0071] The X-ray diffraction patterns of the catalytically active electrodes of Example 1 and Comparative Example 1 are as follows: Figure 1 Shown: From Figure 1 La 0% and Figure 1 La 7.5% comparison shows that Example 1 (corresponding to Figure 1 The high catalytic activity titanium-based lanthanum-doped tin dioxide-antimony electrode and the comparative example 1 (corresponding to Figure 1 The electrodes containing 0% La in the sample have large differences in the X-ray diffraction patterns. Through the analysis of the spectrum data, it is known that the surfaces of the high catalytic activity titanium-based lanthanum-doped tin dioxide-antimony electrode in Example 1 and the comparative example 1 are both well covered with the tin dioxide coating, but there are large differences in the peak intensity and peak position between the two. Calculated by the Scherrer formula, it is known that the crystal size of the titanium-based tin dioxide-antimony electrode is larger than that in Example 1, and the specific surface area is smaller. The surface crystal size of Example 1 is smaller, the surface is more uniform, and the specific surface area is larger. Therefore, the high catalytic activity titanium-based lanthanum-doped tin dioxide-antimony electrode prepared by the present invention has a denser and more uniform electrode coating, a smaller and more uniform crystal size, a larger specific surface area, good electrocatalytic activity and a longer service life.

[0072] Comparative Example 2

[0073] In this comparative example, except that the lanthanum element is replaced by aluminum element (specifically, aluminum nitrate is added), other conditions are the same as those of Example 1.

[0074] The catalytically active electrodes prepared in Examples 1-6 and Comparative Examples 1-2 were tested for electrochemical degradation of norfloxacin solution, and the test results are shown in Table 1. The removal rate curve comparison of the degradation process of antibiotic wastewater simulated by norfloxacin solution for the catalytically active electrodes in Example 1 of the present invention and Comparative Example 1 is shown in Table 1. Figure 2 shown.

[0075] The test method is as follows: the anode is the catalytically active electrode prepared in Examples 1-6 and Comparative Examples 1-2, the cathode is a stainless steel plate, the electrolyte is a mixed solution containing 20 mg / L of norfloxacin and 0.1 mol / L of sodium sulfate, and the current density is 10 mA / cm 2 ,The effective electrolysis area is 20mm X 20mm, the electrode spacing is 2.5cm, and the electrolysis time is 1.5h. The degradation rate of antibiotic wastewater simulated by norfloxacin solution is tested.

[0076] Table 1

[0077] Wastewater degradation rate Example 1 92% Example 2 83% Example 3 78% Example 4 80% Example 5 71% Example 6 75% Comparative Example 1 62% Comparative Example 2 76%

[0078] From the above table, it can be obtained that the degradation rate of wastewater by titanium-based tin dioxide-antimony electrode is affected by many factors. The appropriate addition of lanthanum element in the electrode will significantly improve the degradation rate of wastewater, and excessive doping of lanthanum element will lead to a decrease in the degradation rate of wastewater. Too short a solvent thermal reaction time will reduce the degradation rate of wastewater. The reduction and shortening of calcination temperature and calcination time are also not conducive to the degradation of wastewater by the electrode. Pretreatment is also an important part of electrode preparation. Insufficient pretreatment measures will reduce the degradation rate of wastewater. By comparing Example 1 with Comparative Example 2, it can be seen that the addition of lanthanum is more conducive to the degradation of wastewater by the electrode.

[0079] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A catalytically active electrode, characterized in that: The catalytically active electrode comprises a titanium-based current collector and a lanthanum- and antimony-doped tin dioxide layer located on the titanium-based current collector; The molar ratio of lanthanum to antimony is (5-10):10; The molar percentage of lanthanum in the tin dioxide layer is 1-10%; The catalytically active electrode is prepared by the following method, which includes: placing the titanium-based current collector in a mixed solution containing tin, antimony and lanthanum, performing a solvent thermal reaction at 150-190° C., and calcining to obtain the catalytically active electrode.

2. A method for preparing a catalytically active electrode as claimed in claim 1, characterized in that: The preparation method comprises: The titanium-based current collector is placed in a mixed solution containing tin, antimony and lanthanum, and a solvent thermal reaction is carried out at 150-190° C., followed by calcination to obtain the catalytically active electrode.

3. The preparation method according to claim 2, characterized in that: The preparation method of the mixed solution is: adding a tin source, an antimony source and a lanthanum source into an acidic solution and mixing them to obtain the mixed solution.

4. The preparation method according to claim 3, characterized in that: The tin source includes crystalline tin tetrachloride.

5. The preparation method according to claim 3, characterized in that: The antimony source includes antimony trichloride.

6. The preparation method according to claim 3, characterized in that: The lanthanum source includes a lanthanum salt compound, and the lanthanum salt compound includes lanthanum nitrate and / or lanthanum chloride.

7. The preparation method according to claim 3, characterized in that: The atomic molar concentration ratio of the tin source, the antimony source and the lanthanum source is 100:10:(5-10).

8. The preparation method according to claim 3, characterized in that: The solvent of the acidic solution is an organic solvent, and the organic solvent includes ethanol.

9. The preparation method according to claim 3, characterized in that: The solute of the acidic solution is hydrochloric acid.

10. The preparation method according to claim 9, characterized in that: The concentration of the hydrochloric acid in the mixed solution is 0.5-1 mol / L.

11. The preparation method according to claim 3, characterized in that: The mixing includes ultrasonic mixing.

12. The preparation method according to claim 11, characterized in that: The ultrasonic mixing time is 10 to 30 minutes.

13. The preparation method according to claim 11, characterized in that: The ultrasonic power of the ultrasonic mixing is 350-450W.

14. The preparation method according to claim 2, characterized in that: The titanium-based current collector includes a titanium mesh, a titanium plate or a titanium foil.

15. The preparation method according to claim 2, characterized in that: The titanium-based current collector is pretreated, and the pretreatment includes: first cleaning and then pickling the titanium-based current collector.

16. The preparation method according to claim 15, characterized in that: The first cleaning comprises: sequentially performing acetone ultrasonic cleaning for 10 to 30 minutes, rinsing with anhydrous ethanol and rinsing with deionized water on the titanium-based current collector.

17. The preparation method according to claim 15, characterized in that: The acid in the pickling comprises 10% oxalic acid.

18. The preparation method according to claim 15, characterized in that: The pickling is a slightly boiling heat treatment in acid, and the time of the slightly boiling heat treatment is 1.5 to 2.5 hours.

19. The preparation method according to claim 15, characterized in that: The first cooling is performed after the pickling, and the titanium-based current collector is stored in anhydrous ethanol after the first cooling.

20. The preparation method according to claim 2, characterized in that: The solvent thermal reaction is carried out in a reactor.

21. The preparation method according to claim 2, characterized in that: The solvent thermal reaction time is 8 to 16 hours.

22. The preparation method according to claim 2, characterized in that: After the solvent thermal reaction, second cooling, second cleaning and drying are sequentially performed.

23. The preparation method according to claim 22, characterized in that: The second cleaning includes cleaning the electrode surface with deionized water and / or anhydrous ethanol.

24. The preparation method according to claim 22, characterized in that: The dried electrode is calcined.

25. The preparation method according to claim 24, characterized in that: The calcination atmosphere is air.

26. The preparation method according to claim 24, characterized in that: The calcination temperature is 400-600°C.

27. The preparation method according to claim 24, characterized in that: The calcination time is 1 to 3 hours.

28. A use of a catalytically active electrode as claimed in claim 1, characterized in that: The catalytically active electrode is applied in the technical field of electrochemical water treatment.

Citation Information

Patent Citations

  • Aluminum-doped SnO2 electro-catalytic positive pole, preparation method, and application thereof

    CN106241970A

  • Preparation method of titanium-based lead dioxide anode

    CN108914122A

  • Preparation method of antimony-doped tin oxide electrode with high efficiency and long service life

    CN109264829A